Resin cement coating reverts the machining damage on the flexural fatigue strength of lithium disilicate glass-ceramic - May, Michele Mirian (2023)
This study evaluated the effect of resin cement coating with high and low viscosities on the flexural fatigue strength of machined lithium disilicate glass-ceramic. Discs (IPS e.max CAD; Ivoclar Vivadent) were prepared and divided according to the surface condition (machining [M]—CEREC inLab; and polishing [P]—laboratory procedures), resin cement coating (with or without), and cement viscosity (high [H] and low [L]). The ceramic bonding surface was etched/primed by a one-step primer application followed by resin cement application (Variolink N base + high or low viscosity catalyst; Ivoclar Vivadent). Biaxial flexural fatigue strength was evaluated on a piston-on-three-ball set by the step-test method (n = 15) (initial stress: 60 MPa; incremental steps: 20 MPa; 10,000 cycles/step, at 20 Hz). Weibull statistics were used for fatigue data. Contact angle, topographic, and fractographic analysis were also performed. Machining produced statistically lower contact angle than polishing and a significant detrimental effect on the fatigue behavior (σ0M = 247.2 [246.9–268.3]; σ0P = 337.4 [297.8–382.4]). Machined groups followed by resin cement coating (σ0MH = 297.9 [276.0–321.5]; σ0Ml = 301.2 [277.1–327.4]) behaved similarly to the polished and coated groups (σ0PH = 342.0 [308.9–378.5]; σ0PL = 357.3 [324.7–393.1]), irrespective of the cement viscosity. Therefore, cement coating has able to revert the detrimental effects of the machining on the fatigue strength of lithium disilicate glass-ceramic. High and low viscosity cements behaved similarly in the improvement of CAD–CAM lithium disilicate fatigue strength.